VANISHING RETINAL DETACHMENT - Lalezary, Maziar (Retin Cases Brief Rep, 2015)
The purpose of this report is to describe a case of rhegmatogenous retinal detachment in the setting of chronic kidney disease that exhibited complete retinal reattachment after serial hemodialysis. METHODS: Retrospective case report. RESULTS: A 58-year-old woman with acute vision loss was found to have a macula-involving rhegmatogenous retinal detachment. Due to chronic kidney disease, she continued with routinely scheduled hemodialysis for 1 week until surgical clearance was obtained. Preoperative examination revealed complete reattachment of the retina with a persistent retinal tear. Barrier laser was applied to the tear and the retina remained attached until the most recent follow-up 8 months later. The workup of alternate etiologies was unrevealing. CONCLUSION: This case describes a temporal association between hemodialysis and resolution of subretinal fluid due to rhegmatogenous retinal detachment. A potential causal linkage is suggested based on shifting fluid dynamics associated with hemodialysis. A shift in treatment paradigm is not advised.